A new perspective on special effective interventions for metabolic syndrome risk factors: a systematic review and meta-analysis - Wang, Haonan; Dai, Yinghong; Huang, Sike; Rong, Siyu; Qi, Yufei; Li, Bin (Frontiers in Public Health, 2023)
Metabolic syndrome (MetS) has the largest global burden of all noncommunicable diseases. Owing to the clinical heterogeneity of MetS, wide variations have been reported in the efficacy of moderate-to-vigorous physical activity (MVPA) and intermittent fasting (IF) for improving MetS. We searched five databases for randomized controlled trials published through December 2021, and 372 participants from 11 studies were included in this meta-analysis. Compared with MVPA alone, IF combined with MVPA had a more significant effect on improving body mass and levels of fasting blood glucose and high-density lipoprotein cholesterol; however, it was ineffective in improving triglycerides level, systolic blood pressure, and diastolic blood pressure. Subgroup analysis showed that, except for blood pressure, time-restricted fasting combined with MVPA had a better effect than alternate-day fasting with MVPA. Meanwhile, when the intervention lasted longer than 8 weeks, the effect of the combined intervention was significantly better than that of MVPA alone. This finding provides a basis for clinicians to manage the health of overweight individuals. This study also showed that Caucasians may be more suitable for the combined intervention than Asians. And the combined intervention may provide a preventive effect for MetS risk factors in healthy populations, although this may be due to the small sample size. In general, this study provides a novel perspective on special interventions for MetS traits.